Stimulation of estrus and ovulation in lactating sows - H L Frobose; K M Gourley; Michael D Tokach; Joel M DeRouchey; Steven S Dritz; Robert D Goodband; Jim L Nelssen; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 2013)
A total of 53 sows were used to determine the effects of a lactational estrus stimulation strategy on reproductive and litter growth performance. Treatment differences within parity group, multiparous and primiparous, were also considered. Litter size was equalized to 11.6 ± 1.2 pigs at d 2 postfarrowing. At d 18 of lactation, sows were allotted to the control or an altered suckling method (ALT). The ALT sows were placed in adjacent pairs within parity so pigs could be moved between litters by temporarily lifting the divider between the two litters. On d 18, all but the 5 lightest weight pigs from each ALT litter were weaned. The 5 lightweight pigs for each pair of litters formed a combined litter that nursed each sow of the pair 12 h/d from d 18 to 25. Therefore, pigs had nursing access 24 h/d, but each ALT sow was suckled only 12 h/d. Boar exposure was provided to ALT sows for 15 min/d by removing sows to a pen outside the farrowing room. Control and ALT sows were weaned at d 21 and d 25, respectively. Sow weights and litter growth performance during lactation was similar between treatments, although ALT sows had 16% greater total feed intake (P<0.01) due to the extended lactation length. Primiparous sows lost a greater percentage (7.4 vs. 3.4%) of BW and consumed less feed (P<0.01) than multiparous sows. A total of 26 ALT sows (93%) were detected in estrus and mated in lactation. Although duration from initiating ALT to estrus was greater (P<0.001) than the wean-to-estrus interval for controls, ALT sows were in estrus earlier (23.0 vs. 24.6 d; P<0.001) than controls postfarrowing, with primiparous sows responding more slowly (5.4 vs. 3.8 d; P<0.01) than multiparous sows for both treatments. Pregnancy rate and subsequent reproductive performance were similar between treatments. In conclusion, ALT sows expressed lactational estrus and performed reproductively similar to sows with conventionally weaned litters.; Swine Day, Manhattan, KS, November 21, 2013
Keywords: Swine day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-044-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1092; Boar exposure; Lactating sow; Lactational estrus; Split weaning; Swine